HUBUNGAN PENGETAHUAN IBU TENTANG PERAWATAN PAYUDARA DENGAN KEJADIAN ORAL TRUSH PADA BAYI 0-6 BULAN - Desmawati, Elis (LPPM STIKes Mitra Adiguna, 2025)
Oral thrush (stomatitis) is inflammation of the mouth (on the lips or tongue). This is usually found in babies. According to WHO, the prevalence of stomatitis varies depending on the population of the area studied. The total number of stomatitis diseases is 15-25% of the world population. This study found that the number of stomatitis cases was around 2% in Sweden, 1.9% in Spain and 0.5% in Malaysia. In Indonesia, the prevalence of stomatitis at Ciptomangun Kusumo Hospital is 26.6%, the number of stomatitis cases from 101 patients was 17.3%. To determine the relationship between maternal knowledge about breast care and the incidence of oral thrush in babies 0-6 months. The research was carried out descriptively and analytically by collecting cross-sectional data using questionnaires. The sample used total sampling criteria and obtained 36 respondents. Based on the questionnaire, the distribution of respondents' knowledge was good at 55.6% and the incidence of Oral Trush was 58.3%, however with bivariate analysis there was a significant relationship between maternal knowledge about breast care and the incidence of Oral Trush. There is a relationship between maternal knowledge about breast care and the incidence of oral thrush in babies 0-6 months. Suggestions: action can be taken to improve and change perceptions regarding Breast Care by providing health education, counseling and promotion so that research is carried out on a greater prevalence and supplemented with examinations so that it is certain that the Oral Trush suffered by the respondent.